Social Practices of Students with Disabilities in Inclusive School: A Bourdieusian Analysis of Habitus, Capital, and Field - Supriyanto, Supriyanto; Imron, Ali; Maisyaroh, Maisyaroh; Muslihati, Muslihati; Syarif, Izuddin; Puspitasari, Fantika Febry; Sulaiman, Ahmad (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Establishing inclusive education is essential to achieving equality and fairness, particularly for students with disabilities. The emergence of discrimination has challenged the implementation of social practices in an inclusive school to guarantee the participation of students with disabilities academically and socially. This study empirically examines the social practices of these students within an inclusive school setting through the lens of Pierre Bourdieu’s theory of social practice, focusing on the interplay of habitus, capital, and field. Qualitative methods, employing a case study approach, were utilized. The case study was conducted at Muhammadiyah 2 Junior High School in Malang, an inclusive school that has developed various innovative programs to optimize the education of students with disabilities. Data were gathered through in-depth interviews, participatory observation, and documentary analysis. The findings indicate that: (1) The unique habitus of students with disabilities shaped by family background and life experiences significantly influences their adaptation and self-perception; (2) Students strategically utilize various forms of capital (social, cultural, and symbolic) to navigate and integrate into the school environment; and (3) The school as a field through policies, teacher and principal roles, and social structures plays a critical role in enabling or constraining participation and inclusion. The study concludes that the dynamic interaction between habitus, capital, and field profoundly shapes the ability of students with disabilities to form relationships and construct their identities in inclusive educational contexts. These findings underscore the need for comprehensive policy interventions, teacher professional development, and ongoing institutional support to create truly inclusive environments. Recommendations for future research include exploring the long-term sustainability of such models and their applicability across diverse socio-cultural settings.